Utilizing Non-Orthogonal Multiple Access for Both Latency and Energy Efficiency Improvement in TSCH-Based WSNs - Nasrin Gholami; Neda Moghim; Mahdieh Ghazvini; Sasan Haghani (IEEE Access, 2022)
Non-Orthogonal Multiple Access (NOMA) is one of the promising technologies for wireless communication networks. Although NOMA was originally proposed in cellular networks, due to its strengths, it can also be used in other networks, such as wireless sensor networks (WSN). Massive connections and energy limitations are some of the challenges in WSNs and NOMA can be used to improve spectral efficiency, reduce latency, and increase energy efficiency of these networks. In this paper, we investigate the effect of Power-Domain NOMA (PD-NOMA) on the performance of IEEE 802.15.4e Time Slotted Channel Hopping (TSCH)-Based WSNs. A clustered WSN is studied in which sensor nodes send their data to their cluster heads using NOMA transmissions, and where the cluster heads will also utilize NOMA for the transmission of their aggregated data to the sink node. A fair user grouping and power allocation scheme is proposed in PD-NOMA where the users utilizing the same channel and their corresponding power levels are determined. A new clustering algorithm is also proposed to select the appropriate cluster heads for the NOMA transmission. Simulation results show that the proposed scheme improves energy efficiency, latency, and network throughput in IEEE 802.15.4e TSCH-based WSNs.